Treatment with tumour necrosis factor inhibitor oxpentifylline does not improve corticosteroid dependent chronic active Crohn's disease. Issue 4 (April 1997) - Bauditz, J; Haemling, J; Ortner, M; Lochs, H; Raedler, A; Schreiber, S
Abstract : BACKGROUND: In Crohn's disease, inflammation is presumably sustained by an increased production of proinflammatory cytokines, in particular tumour necrosis factor alpha (TNF alpha) and interleukin 1 beta (IL 1 beta). TNF alpha can induce a host of cellular effector events resulting in perpetuation of the inflammatory process. In vivo studies with anti-TNF alpha antibody treatment have led to impressive clinical results. AIMS: To investigate whether treatment with the TNF alpha inhibitor oxpentifylline results in clinical improvement in corticosteroid dependent chronic active Crohn's disease. METHODS: Sixteen Crohn's disease patients received oxpentifylline 400 mg four times a day in a four week open label study. RESULTS: Blockade of TNF alpha production in 16 patients with corticosteroid dependent Crohn's disease did not improve the clinical disease activity (CDAI mean (SEM) 188.75 (5.65) versus 185.13 (10.87) or the endoscopic degree of inflammation (CDEIS 14.9 (2.87) versus 14.8 (2.27) or laboratory parameters. CONCLUSIONS: In this study, use of the TNF alpha inhibitor oxpentifylline does not improve inflammation in Crohn's disease. This finding suggests that there may be more key mediators than only TNF alpha in the inflammatory process in Crohn's disease.